Justiciabilidad de los derechos sociales - Gabriel Galán Melo (Ius Humani. Jornal do direito, 2016)
Since 2000, social rights have gained prominence in our countries (Andean countries), inside the Doctrine, and in the worldwide and regional organizations, for the protection of human rights. These have been raised as apparent leveling mechanisms between the real freedom of each of the individuals and legal freedom, that the constitutional and legal framework recognizes them. In Latin America, due to considerable levels of inequality and poverty, an effective model of comprehensive and reasonable social rights, that can really ensure the factual freedom of all citizens alike are looking for. So, the imposition of a single model that reaches theoretically equate factual or real freedom of all citizens, but one that also ensure, its justiciability despite the implications that would result in the budgetary policy of the state is not enough. Thus, it seems relevant the creation of a Latin American Doctrine on social rights, taking into consideration that a latent danger that lurks behind the discourse of such rights is the social demobilization caused by the Latin neopopulism and should propose, in this case, the construction of a national system for optimal protection with additional security systems, regionally and internationally protection and its appropriation by the population in the political and legal practice. It means, an integrated multi-level social rights protection system.